2019
DOI: 10.1002/slct.201903064
|View full text |Cite
|
Sign up to set email alerts
|

An Imidazo[1,2‐a]pyridine Derivative That Enables Selective and Sequential Sensing of Cu2+ and CN Ions in Aqueous and Biological Samples

Abstract: We report a triazole appended imidazopyridine based chemosensor (probe 1) for sequential detection of Cu2+ and CN− ions using fluorometry. Probe 1 is fluorescent in aqueous acetonitrile (H2O‐CH3CN, 1:1, v/v) when common metal ions are present, but the fluorescence is quenched when Cu2+ is present. The binding mechanism, quantitative determination and the mode of interaction of Cu2+ with probe 1 are explained using fluorescence spectroscopy, electrospray ionization mass spectrometry and Density Functional Theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 62 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…We recently observed that presence of two donor atoms in a chemosensor is sufficient to impart selective binding with specific metal ions [39,40] . In our on‐going effort to develop chemosensors for naked‐eye detection, [38,41,42] we envisaged that compound A would be a suitable candidate for probing specific metal ions as the intramolecular H‐bonding vis‐à‐vis the tautomerisomerization (Scheme 1) would influence metal ion selective binding.…”
Section: Resultsmentioning
confidence: 99%
“…We recently observed that presence of two donor atoms in a chemosensor is sufficient to impart selective binding with specific metal ions [39,40] . In our on‐going effort to develop chemosensors for naked‐eye detection, [38,41,42] we envisaged that compound A would be a suitable candidate for probing specific metal ions as the intramolecular H‐bonding vis‐à‐vis the tautomerisomerization (Scheme 1) would influence metal ion selective binding.…”
Section: Resultsmentioning
confidence: 99%